Assessing physical performance and physical activity in large population-based aging studies: home-based assessments or visits to the research center? - Erja Portegijs; Laura Karavirta; Milla Saajanaho; Timo Rantalainen; Taina Rantanen (BMC, 2019)
Abstract Background The current study aims to compare correlations between a range of measures of physical performance and physical activity assessing the same underlying construct in different settings, that is, in a home versus a highly standardized setting of the research center or accelerometer recording. We also evaluated the selective attrition of participants related to these different settings and how selective attrition affects the associations between variables and indicators of health, functioning and overall activity. Methods Cross-sectional analyses comprising population-based samples of people aged 75, 80, and 85 years living independently in Jyväskylä, Finland. The AGNES study protocol involved the following phases: 1) phone interview (n = 1886), 2) face-to-face at-home interview (n = 1018), 3) assessments in the research center (n = 910), and 4) accelerometry (n = 496). Phase 2 and 3 included walking and handgrip strength tests, and phase 4 a chest-worn and thigh-worn accelerometer estimating physical activity and assessing posture, respectively, for 3-10 days in free-living conditions. Results Older people with poorer health and functioning more likely refrained from subsequent study phases, each requiring more effort or commitment from participants. Paired measures of walking speed (R = 0.69), handgrip strength (R = 0.85), time in physical activity of at least moderate intensity (R = 0.42), and time in upright posture (R = 0.30) assessed in different settings correlated with each other, and they correlated with indicators of health, functioning and overall activity. Associations were robust regardless of limitations in health and functioning, and low overall activity. Conclusions Correlational analyses did not clearly reveal one superior setting for assessing physical performance or physical activity. Inclusion of older people with early declines in health, functioning and overall activity in studies on physical performance and physical activity is feasible in terms of study outcomes, but challenging for recruitment.